2020
DOI: 10.3390/w12092487
|View full text |Cite
|
Sign up to set email alerts
|

Using Stable Isotope Analysis (δD and δ18O) and Tracing Tests to Characterize the Regional Hydrogeological Characteristics of Kazeroon County, Iran

Abstract: Unpredictable climate changes are affecting water resources, especially in karst arid and semiarid areas. In such locations, the need for additional sources of water always arises. The paper gives insight into hydrogeological characteristics of Kazeroo County and resolves some unknowns around the catchment area of the springs important for water supply of the wider urban area of the city of Kazeroon, Iran, by using stable isotope analysis (δD and δ18O) and tracer test. Multiple tracer test and stable isotope a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…According to the studies of [36], the reaction time of Sasan spring to maximum rainfall events is from 6 to 85 days with an average of 43 days, its memory effect using ACF is 90 days and, based on CCF, the reaction time for quick flow and base flow is estimated at 18 and 58 days, respectively. It is reported that this spring has a conduit flow type [37]. Rain recording stations were selected for this study based on the closest measuring station of meteorological parameters to the area where each spring appeared (Table 1).…”
Section: Study Areamentioning
confidence: 99%
“…According to the studies of [36], the reaction time of Sasan spring to maximum rainfall events is from 6 to 85 days with an average of 43 days, its memory effect using ACF is 90 days and, based on CCF, the reaction time for quick flow and base flow is estimated at 18 and 58 days, respectively. It is reported that this spring has a conduit flow type [37]. Rain recording stations were selected for this study based on the closest measuring station of meteorological parameters to the area where each spring appeared (Table 1).…”
Section: Study Areamentioning
confidence: 99%
“…Hua et al [21] developed an innovative dimension reduction model (DRM) based on tracer test results, which effectively characterizes fractured networks and predicts the flow and transport within the fractured aquifers, further demonstrating its applicability to fractured network characterization at the field scale. Dogančić et al [22] established the hydraulic connectivity between Shahneshin North and Dashtak North through the use of stable isotope analysis (δD and δ 18 O) alongside multiple tracer tests.…”
Section: Introductionmentioning
confidence: 99%
“…Dogančić et al [4] presented several investigation actions performed to better characterize the hydrogeological characteristics of Kazeroo County (Iran). The new knowledge is of significant importance for managing the karst aquifer for water supply purposes.…”
mentioning
confidence: 99%